Evaluation of the protective effect of Clitoria ternatea L. against propionic acid induced autistic spectrum disorders in rat model - Jiji, K. N. (2023)
As a result of aberrant neural development, autism spectrum disorder (ASD) is characterised by complicated behavioural and memory issues. The dearth of knowledge about the actual etiopathology of autism makes treatment extremely difficult. There is a collection of plants known as "Medhya drugs" in the Ayurvedic system of medicine because of their capacity to boost brain and neuron-related activities including learning and memory. Clitoria ternatea L. is a "Medhya drug" that has been shown to improve memory. In this study, the ethanolic root extract of Clitoria ternatea L. was evaluated for its neuroprotective effects against propionic acid induced neuroinflammation in autistic rat modells.